Nutrition behaviour change communication causes sustained effects on IYCN knowledge in two cluster-randomised trials in Bangladesh - Hoddinott, John F.; Ahmed, Akhter; Karachiwalla, Naureen; Roy, Shalini (Wiley, 2018)
Behaviour change communication (BCC) can improve infant and young child nutrition (IYCN) knowledge, practices, and health outcomes. However, few studies have examined whether the improved knowledge persists after BCC activities end. This paper assesses the effect of nutrition sensitive social protection interventions on IYCN knowledge in rural Bangladesh, both during and after intervention activities. We use data from two, 2-year, cluster randomised control trials that included nutrition BCC in some treatment arms. These data were collected at intervention baseline, midline, and endline, and 6–10 months after the intervention ended. We analyse data on IYCN knowledge from the same 2,341 women over these 4 survey rounds. We construct a number correct score on 18 IYCN knowledge questions and assess whether the impact of the BCC changes over time for the different treatment groups. Effects are estimated using ordinary least squares accounting for the clustered design of the study. There are 3 main findings: First, the BCC improves IYCN knowledge substantially in the 1st year of the intervention; participants correctly answer 3.0–3.2 more questions (36% more) compared to the non-BCC groups. Second, the increase in knowledge between the 1st and 2nd year was smaller, an additional 0.7–0.9 correct answers. Third, knowledge persists; there are no significant decreases in IYCN knowledge 6–10 months after nutrition BCC activities ended.